Characterization of the genetic factors affecting quinolizidine alkaloid biosynthesis and its response to abiotic stress in narrow‐leafed lupin (Lupinus angustifolius L.). (10th May 2018) - Frick, Karen M.; Foley, Rhonda C.; Kamphuis, Lars G.; Siddique, Kadambot H.M.; Garg, Gagan; Singh, Karam B.
Abstract: Quinolizidine alkaloids (QAs) are toxic secondary metabolites that complicate the end use of narrow‐leafed lupin (NLL; Lupinus angustifolius L.) grain, as levels sometimes exceed the industry limit for its use as a food and feed source. The genotypic and environmental influences on QA production in NLL are poorly understood. Here, the expression of QA biosynthetic genes was analysed in vegetative and reproductive tissues of bitter (high QA) and sweet (low QA) accessions. It was demonstrated that sweet accessions are characterized by lower QA biosynthetic gene expression exclusively in leaf and stem tissues than bitter NLL, consistent with the hypothesis that QAs are predominantly produced in aerial tissues and transported to seeds, rather than synthesized within the seed itself. This analysis informed our identification of additional candidate genes involved in QA biosynthesis. Drought and temperature stress are two major abiotic stresses that often occur during NLL pod set. Hence, we assessed the effect of drought, increased temperature, and their combination, on QA production in three sweet NLL cultivars. A cultivar‐specific response to drought and temperature in grain QA levels was observed, including the identification of a cultivar where alkaloid levels did not change with these stress treatments. Abstract : Narrow‐leafed lupin grain is an emerging human health food; however, toxic quinolizidine alkaloids in the grain sometimes exceed acceptable levels for food purposes, with little known about the genetic and environmental factors that increase alkaloid levels. This research measured the extent of quinolizidine alkaloid biosynthesis within tissues of narrow‐leafed lupin, which allowed us, in conjunction with newly available transcriptomic and genomic data for the crop, to identify candidate genes involved in quinolizidine alkaloid biosynthesis. We then measured the response of quinolizidine alkaloid biosynthesis and accumulation in narrow‐leafed lupin to two abiotic stresses often imposed upon the crop: drought and increased temperature. We identified that the response of grain alkaloid levels to these stresses is cultivar‐dependent, including the identification of one cultivar for which grain alkaloid levels do not increase in response to these stresses.